A note on the consolidation settlement of a rigid circular foundation on a poroelastic halfspace. (14th March 2016) - Kim, Jueun; Selvadurai, A.P.S.
Summary: This paper uses Biot's poroelasticity approach to examine the consolidation behaviour of a rigid foundation with a frictionless base in contact with a poroelastic halfspace. The mathematical development of the mixed boundary value problem involves a set of dual integral equations in the Laplace transform domain which cannot be conveniently solved by employing conventional procedures. In this paper, a numerical solution is developed using a scheme where the contact normal stress is approximated by a discretized equivalent. The influence of limiting drainage boundary conditions at the entire surface of the halfspace on the degree of consolidation of the rigid circular foundation is investigated. The results obtained in this study are compared with the corresponding results given in the literature. Copyright © 2016 John Wiley & Sons, Ltd.